Method for manufacturing long-term use high temperature and high humidity environment resistant self-adhesive automobile color-changing film

CN122770239APending Publication Date: 2026-09-18王建国
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610957423.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0005](2)现有专利技术未解决残胶问题;

Benefits of technology

(1)彻底解决高温高湿环境下的残胶问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122770239A_ABST
    Figure CN122770239A_ABST
Patent Text Reader

Abstract

The application discloses a manufacturing method of a long-term self-adhesive automobile color-changing film resistant to high-temperature and high-humidity environment, and the color-changing film comprises a surface layer, a white support layer, a resistant support layer and a hot melt pressure-sensitive adhesive layer. The hot melt pressure-sensitive adhesive layer is formed by hydrogenated styrene block elastomer and hydrogenated aliphatic C5 petroleum resin through DCP chemical crosslinking or electron beam irradiation crosslinking to form a three-dimensional network structure, thereby improving cohesion and avoiding residual glue in a high-temperature and high-humidity environment. The surface layer and the support layer are added with an organic barrier agent BETT-68 to slow down water vapor permeation. The crosslinking agent and the antioxidant are added in two stages to avoid mutual interference of free radicals. Inorganic microbeads are added to the hot melt pressure-sensitive adhesive to facilitate secondary film pasting and air exhaust, and a scratch-resistant agent FF-99 is added to the surface layer to improve scratch resistance. The application solves the problem of residual glue of polyolefin color-changing film after long-term use in a tropical or subtropical region, and the color-changing film can be used for more than five years in a high-temperature and high-humidity environment without residual glue, thereby meeting the stringent test requirements of the general motor standard GMW16865-2017.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive paint protection technology, and in particular to a method for manufacturing a self-adhesive automotive paint color-changing film that can be used for a long time and is resistant to high temperature and high humidity environments. Background Technology

[0002] With the continuous development of the domestic economy, the automotive industry has made significant progress. According to reports, passenger vehicle production is projected to reach 30.27 million units in 2025, with sedan production nearing 12 million units. Assuming an annual demand of 5% of this 12 million units, this would require 14.4 million square meters of color-changing film. In recent years, it is expected that many customers will opt for color-changing film, making the outlook very optimistic. Even older vehicles will require color-changing film, so the demand is substantial.

[0003] Currently, commonly used self-adhesive automotive paint color-changing films generally adopt a three-layer structure, which can be formed using three-layer co-extrusion casting or blown film equipment. The hot-melt pressure-sensitive adhesive typically accounts for about 10% of the total thickness, using hydrogenated styrene block elastomers (SEBS or SEPS) and hydrogenated aliphatic C5, C9, C5 / C9 petroleum resins, etc.; the intermediate support layer accounts for about 80% of the total thickness, using polypropylene homopolymer, polypropylene copolymer, polyolefin elastomer, metallocene low-density polyethylene, linear low-density polyethylene, low-density polyethylene, titanium dioxide, etc.; the surface layer accounts for about 10% of the total thickness, using linear low-density polyethylene, low-density polyethylene, high-density polyethylene, polypropylene, and white or various colored masterbatches, etc.

[0004] However, the aforementioned existing technologies have the following shortcomings: (1) The problem of residual adhesive is prominent under high temperature and high humidity conditions; Automotive paint color-changing films manufactured according to the above materials and usage ratios often fail tests under relatively harsh conditions. For example, according to General Motors standard GMW16865-2017, after the substrate sample with the color-changing film applied is placed in an air-circulating oven at 85℃±2℃ for 336 hours, and then the film is removed to inspect the substrate's appearance, residual adhesive is often found, resulting in failure. Similarly, in the GMW14124 cycle I high-temperature and high-humidity environmental test (80℃ / 16h→38℃ / approximately 100%RH / 24h→-30℃ / 8H, a total of 5 cycles), residual adhesive also leads to failure.

[0005] (2) Existing patented technologies have not solved the problem of residual adhesive; A search revealed that Japanese patent application JP2000-33671 discloses a self-adhesive color-changing film for protecting automotive paint surfaces. The film uses a mixture of polypropylene or copolymer and polyethylene as the substrate, and the hot melt pressure-sensitive adhesive uses a mixture of SEBS and alicyclic tackifying resin. However, this patent does not address solutions for situations where there is residual adhesive in low-latitude tropical or subtropical regions with high temperature and humidity and long-term use. Furthermore, no commercial products are available on the market.

[0006] (3) Defects exist in coated products; The most common car paint changer films on the market are manufactured using a coating process. A European company selling polyisobutylene-coated color changer films in China, employing a solvent-based coating process, frequently experienced delamination and residue issues, and the processing method was also environmentally unfriendly. Another European company also sold self-adhesive color changer films in China; although produced using a dry process, the hot-melt pressure-sensitive adhesive was outsourced, lacking independent R&D capabilities, resulting in residue issues and its withdrawal from the market. Chinese patent CN105802554B discloses a pressure-sensitive adhesive for color changer films that is resistant to damp heat aging and leaves no residue, using a solvent-based acrylic pressure-sensitive adhesive system, representing a different technological approach. Data shows that damp heat residue is difficult to resolve.

[0007] (4) Domestic market gap; There are no reports in the domestic market of self-adhesive automotive paint color-changing films that can be used in low-latitude tropical or subtropical regions with high temperature and humidity and long-term use.

[0008] Chinese patent CN103865428B discloses a method for preparing electron beam cured hot melt pressure-sensitive adhesive, but it uses a tackifier copolymerized from aliphatic C5 and aromatic C9, which carries a risk of precipitation. It only performs tests at 80°C and lacks a double 85 test (85°C / 85%RH). Chinese patent CN107629726B uses DCP crosslinking and only verifies no residue under 100°C high temperature (100°C dry heat) conditions, without covering high humidity environment testing. Chinese patent CN110527454B uses the tackifier Escorez2203. Because 2203 contains aromatic structures, it has poor photothermal stability and insufficient resistance to damp heat residue. Its damp heat aging test only reaches 80°C / 90%RH, making it unsuitable for long-term outdoor use.

[0009] (5) The existing three-layer co-extruded structure has insufficient barrier performance; Existing technologies mostly adopt a three-layer co-extrusion structure, lacking the synergistic effect of an independent sun-resistant barrier layer and a white reflective layer. Water vapor can easily penetrate into the hot-melt pressure-sensitive adhesive layer, leading to a decrease in cohesion and the generation of residual adhesive in high-temperature and high-humidity environments.

[0010] Therefore, there is an urgent need to develop a car paint color-changing film that can be used for more than five years in high temperature and high humidity environments without producing adhesive residue. Summary of the Invention

[0011] To address the problems existing in the prior art, the first objective of this invention is to provide a method for manufacturing a self-adhesive automotive color-changing film that can withstand high temperature and high humidity environments for long-term use, and the second objective is to provide a self-adhesive automotive color-changing film that can withstand high temperature and high humidity environments for long-term use.

[0012] To achieve the aforementioned first objective, the present invention provides a technical solution for manufacturing a self-adhesive automotive color-changing film that can withstand high temperature and high humidity environments for long-term use. The color-changing film includes a surface layer, a support layer, and a hot melt pressure-sensitive adhesive layer. The hot melt pressure-sensitive adhesive layer is cross-linked to form a chemical bond network structure, which improves cohesion and avoids the generation of residual adhesive when pasting on the automotive paint surface in a high temperature and high humidity environment. The crosslinking treatment forms a three-dimensional network structure in the hot melt pressure-sensitive adhesive, which is composed of polymer molecular chains connected by covalent bonds. The three-dimensional network structure inhibits the thermal motion and thermal oxidative degradation of molecular chains under high temperature conditions, and resists the plasticizing effect of water molecules on molecular chains under high temperature and high humidity conditions, thereby maintaining the cohesive stability of the hot melt pressure-sensitive adhesive.

[0013] Preferably, the hot-melt pressure-sensitive adhesive layer is formed by mixing hydrogenated styrene block elastomer and hydrogenated petroleum resin and then cross-linking the mixture to form the chemical bond network structure.

[0014] Preferably, the hydrogenated petroleum resin is a hydrogenated aliphatic C5 petroleum resin.

[0015] Preferably, the support layer includes a white support layer and a sun-resistant support layer; preferably, the white support layer is a support layer containing titanium dioxide to block UV irradiation and enhance the surface color, and the sun-resistant support layer is a support layer containing sun-resistant carbon black to block UV.

[0016] Preferably, the crosslinking treatment is performed by chemical crosslinking using peroxide as a crosslinking agent, or by physical crosslinking using irradiation.

[0017] Preferably, the peroxide is dicumyl peroxide (DCP).

[0018] Preferably, the irradiation is electron beam irradiation.

[0019] Preferably, the chemical crosslinking using dicumyl peroxide (DCP) as a crosslinking agent refers to: mixing DCP with hydrogenated styrene block elastomer and hydrogenated aliphatic C5 petroleum resin, and then decomposing DCP during high-temperature extrusion granulation to generate free radicals, which initiate crosslinking reactions between styrene block elastomer molecular chains, forming a three-dimensional network structure composed of carbon-carbon crosslinking bonds; preferably, the amount of DCP added is 0.2% to 0.4%.

[0020] Preferably, the physical crosslinking using electron beam irradiation refers to: granulating a mixture of hydrogenated styrene block elastomer and hydrogenated aliphatic C5 petroleum resin and then irradiating it with an electron beam to directly generate free radicals on the polymer molecular chains and cause a crosslinking reaction, forming a three-dimensional network structure; preferably, the energy of the electron beam irradiation is 40 kGy, and the accumulation thickness of the irradiated material does not exceed 10 cm.

[0021] Preferably, the color-changing film is formed in one step by a co-extrusion blow molding film forming process. The surface layer, the support layer and the hot melt pressure-sensitive adhesive layer are respectively fed by their respective extruders and then combined by a co-extrusion die to form the film.

[0022] Preferably, the co-extrusion blow molding film forming process is a four-layer co-extrusion blow molding film forming process, wherein the surface layer, white support layer, sun-resistant support layer and hot melt pressure-sensitive adhesive layer are respectively fed by their respective extruders, and are combined by the four-layer co-extrusion die to form a four-layer color-changing film.

[0023] Preferably, the process also includes a PET film lamination process: after the four co-extrusion dies are combined into four color-changing films, one side of the surface of the four color-changing films is laminated with a PET film on a hot melt lamination machine equipped with heated mirror rollers.

[0024] Preferably, an antioxidant is added to the cross-linked hot melt pressure-sensitive adhesive particles, preferably including a hindered phenolic primary antioxidant and a thioester secondary antioxidant; preferably, the hindered phenolic primary antioxidant AO-80 is added at an amount of 0.3% to 0.4%, and the thioester secondary antioxidant 412S is added at an amount of 0.3% to 0.4%.

[0025] Preferably, in order to prevent the free radicals generated by the peroxide and antioxidant from reacting with each other and causing a decrease in crosslinking density when they are added at the same time, the addition of the peroxide and antioxidant is carried out in two stages: in the first stage, after adding dicumyl peroxide, the crosslinking is completed by extrusion granulation; in the second stage, the antioxidant is added before film formation.

[0026] Preferably, electron beam irradiation crosslinking can be carried out in one stage, that is, the antioxidant is mixed evenly with SEBS and C5, granulated and then directly irradiated for crosslinking; or it can be carried out in two stages: first, irradiation crosslinking is carried out without adding antioxidant to ensure crosslinking density, and then antioxidant is added.

[0027] Preferably, a hindered amine light stabilizer and a compound antioxidant are added to the surface layer and support layer of the color-changing film, respectively, to synergistically work with the antioxidant in the cross-linked hot melt pressure-sensitive adhesive to reduce thermal oxidative degradation; preferably, the hindered amine light stabilizer is UV3346, with an addition amount of 0.3% to 0.4%, and the compound antioxidant is S2225P, with an addition amount of 0.4% to 0.8%.

[0028] Preferably, a color masterbatch with a required sun resistance rating of level 8 is added to the surface layer of the color-changing film, and a white masterbatch with a titanium dioxide concentration of 65% is added to the white support layer to help block UV radiation. The addition of white masterbatch can also complement the various colors of the surface layer. Preferably, the amount of white masterbatch added is 15%. And / or a carbon black masterbatch with a sun-resistant carbon black concentration of 30% is added to the sun-resistant support layer to block ultraviolet rays. Preferably, the amount of carbon black masterbatch added is 8%. And / or to improve the easy unwinding performance of the color-changing film during application, an ethylene-organic silicone copolymer is added to the surface layer. Preferably, the amount added is 10% to 20%.

[0029] Preferably, an organic barrier agent is added to the surface and support layers of the color-changing film to slow down the penetration of water vapor into the hot melt pressure-sensitive adhesive and prevent the plasticizing effect of water molecules from causing the breakage of the SEBS material chain; preferably, the organic barrier agent is BETT-68, and the amount added is 2.0% to 12.0%.

[0030] Preferably, a scratch-resistant agent is added to the surface of the color-changing film to improve the scratch resistance of the polyolefin; preferably, the scratch-resistant agent is FF-99 or ultra-high molecular weight polyethylene X188, and the amount added is 3%.

[0031] Preferably, the support layer is a mixture of mLLDPE, LLDPE and LDPE, and preferably, the tensile strength of the color-changing film is greater than 20 MPa and the elongation at break is greater than 500%.

[0032] Preferably, inorganic microspheres are added to the hot melt pressure-sensitive adhesive, and preferably, the microspheres have a diameter of 16 μm and an addition amount of 0.3%.

[0033] To achieve the second objective of this invention, the present invention provides a technical solution for a self-adhesive automotive color-changing film that can withstand long-term use in high-temperature and high-humidity environments, comprising a co-extruded structure of a surface layer, a support layer, and a hot-melt pressure-sensitive adhesive layer; the hot-melt pressure-sensitive adhesive layer is cross-linked to form a three-dimensional network structure, which is formed by polymer molecular chains connected by covalent bonds; preferably, the hot-melt pressure-sensitive adhesive layer shows no adhesive residue after undergoing a GMW16865 heat aging test at 85℃±2℃ / 336h and a GMW14124 cycle I high-temperature and high-humidity environment test.

[0034] Preferably, the hot melt pressure-sensitive adhesive layer has a three-dimensional network structure formed by cross-linking hydrogenated styrene block elastomer and hydrogenated petroleum resin.

[0035] Preferably, the hydrogenated petroleum resin is a hydrogenated aliphatic C5 petroleum resin.

[0036] Preferably, the support layer comprises a white support layer and a sun-resistant support layer; the white support layer contains rutile titanium dioxide, and the sun-resistant support layer contains sun-resistant carbon black; the surface layer and / or the white support layer and / or the sun-resistant support layer contain the organic barrier agent BETT-68; the surface layer contains the scratch-resistant agent FF-99; the surface layer contains an ethylene-organosilicon copolymer; The color-changing film showed no adhesive residue after undergoing the GMW16865, 85℃±2℃ / 336h thermal aging test and the GMW14124 cycle I high temperature and high humidity environment test, and can be used for more than five years.

[0037] Preferably, the hot melt pressure-sensitive adhesive layer also contains inorganic microspheres, and preferably, the diameter of the inorganic microspheres is 16 μm and the amount added is 0.3%.

[0038] Optionally, a PET film layer may also be included, which is laminated with the surface layer to improve the surface smoothness and increase the gloss of the color-changing film.

[0039] To clearly illustrate the technical solution of the present invention, the technical principles of the present invention are further explained as follows: 1. Regarding the crosslinking technology of hot melt pressure-sensitive adhesives; The core technology of this invention lies in forming a three-dimensional network structure of hot melt pressure-sensitive adhesive through chemical cross-linking or physical cross-linking, thereby fundamentally solving the problem of residual adhesive in high temperature and high humidity environments.

[0040] Regarding crosslinking degree control: The amount of DCP used must be strictly controlled. The DCP addition should be 0.2% or 0.3%. If it is less than 0.2%, the degree of crosslinking is insufficient, and there will still be residual adhesive when making the sample film; if it is greater than 0.3%, although there is no residual adhesive, the peel strength will be significantly reduced. When the DCP concentration is 0.2%, the gel content is about 30-50% (tested according to GB / 18474, degree of crosslinking according to ASTM D2765).

[0041] 1.2 Regarding electron beam irradiation crosslinking; Electron beam crosslinking utilizes a high-energy electron beam (50–150 kGy) to irradiate SEBS / C5 resin mixtures, generating free radicals on the polymer molecular chains. SEBS itself lacks unsaturated double bonds; therefore, electron beam crosslinking primarily occurs on the butene segments of the rubber phase, forming a three-dimensional network. The key mechanism is that electron beam crosslinking increases the cohesive strength of the adhesive and inhibits molecular chain flow at high temperatures, thereby preventing residual adhesive. Compared to chemical crosslinking, electron beam crosslinking has the following characteristics: The reaction is completed instantly: the free radicals generated by electron beam irradiation complete the cross-linking reaction in a very short time, avoiding competition with antioxidants.

[0042] The process is simple: the antioxidant can be mixed evenly with SEBS and C5 before electron beam irradiation crosslinking, without the need for step-by-step operations.

[0043] Uniform cross-linking: Electron beams have good penetrability and can generate free radicals uniformly inside the material, forming a uniform cross-linking network.

[0044] 2. Principle of two-stage crosslinking process; When DCP and antioxidants are added simultaneously to a hot-melt pressure-sensitive adhesive formulation, complex chemical reactions occur during screw extrusion under heating conditions, affecting the efficiency of DCP and reducing the crosslinking density. This is because: the free radicals generated by the decomposition of DCP react with antioxidant molecules, consuming the free radicals that would otherwise be used for crosslinking; and the antioxidants capture the free radicals generated by DCP, inhibiting the crosslinking reaction.

[0045] Therefore, this invention employs a two-stage method of adding DCP and antioxidants separately: First stage: DCP is added to the formulation and granulated in a twin-screw extruder. At this stage, the DCP has fully completed the cross-linking reaction, the free radicals in the system have been completely consumed, and the cross-linked network has been stably formed.

[0046] The second stage involves adding powdered antioxidants to the pre-formed hot-melt pressure-sensitive adhesive granules and mixing them thoroughly. Finally, the mixture is formed in a casting or blown film equipment. At this point, the SEBS network has been formed, and the C5 resin and antioxidants cannot interfere with the chemical cross-linking. They only play a role in uniformly penetrating and dispersing within the cross-linked SEBS network, thus increasing adhesion, plasticizing, and preventing oxidation.

[0047] The core advantage of the two-step crosslinking method lies in avoiding the interference of C5 resin and antioxidants on the chemical crosslinking reaction, ensuring that the final material has both excellent crosslinking and bonding properties.

[0048] 3. The working principle of the organic barrier agent BETT-68; Under the influence of temperature and humidity, water vapor can penetrate into the hot melt pressure-sensitive adhesive after passing through the surface and intermediate layers. The water vapor acts as a plasticizer, increasing the distance between molecular chains. At the same time, high temperature accelerates the thermo-oxidative aging reaction of molecular chains, leading to the breakage of carbon-carbon bonds and causing chain breakage in materials such as SEBS, thereby reducing the cohesive force of the hot melt pressure-sensitive adhesive.

[0049] When BETT-68 is added to PE film, its oxygen permeability decreases by approximately 25-30%, and its water vapor permeability decreases by approximately 20-25%. The principle behind this is its ability to regulate the crystallization behavior of polyolefins, promoting the formation of finer, more uniform crystalline regions. The tightly packed molecules within these crystalline regions effectively block the penetration of gas and liquid molecules, while the amorphous regions between the crystalline regions also provide some barrier effect due to the filling and interpenetration of BETT-68. BETT-68 can increase the crystallinity of PE by approximately 3-5% and reduce the size of the crystalline regions by approximately 10-15%, further enhancing its barrier properties.

[0050] Adding highly transparent and glossy scratch-resistant agent FF-99 or ultra-high molecular weight polyethylene scratch-resistant agent X188 to the surface of the color-changing film significantly improves the scratch resistance of polyolefins; tests show that adding 3% of scratch-resistant agent FF-99 or X188 can achieve a scratch resistance level of 10N.

[0051] 4. The working principle of inorganic glass microspheres; Currently, applying color-change films to car paint surfaces is still mainly done manually, and inaccurate application often necessitates reapplication. To address the issue of excessive peeling force during reapplication causing severe deformation of the color-change film, a small amount of fine inorganic glass microspheres is added to the hot-melt pressure-sensitive adhesive.

[0052] However, when it is necessary to peel off the color-changing film, the microbeads act as a fulcrum, reducing the actual contact area between the pressure-sensitive adhesive and the paint surface, reducing the peeling force, and making the color-changing film easy to peel off without deformation.

[0053] When the diameter of the microspheres is 16μm, the fulcrum effect is not obvious if it is too small (<10μm), and it may affect the adhesive performance of the pressure-sensitive adhesive if it is too large (>30μm). The optimal amount of microspheres added is 0.3%. Too little microspheres will not have an obvious effect, while too much microspheres may reduce the cohesive force of the pressure-sensitive adhesive.

[0054] By adopting the above technical solution, the beneficial effects achieved by the present invention are as follows: (1) Completely solve the problem of residual adhesive under high temperature and high humidity conditions; Through chemical crosslinking with dicumyl peroxide (DCP) or electron beam irradiation crosslinking, a three-dimensional network structure is formed in the mixture of SEBS / SEPS and C5 petroleum resin, significantly improving the cohesive force of the hot melt pressure-sensitive adhesive and preventing molecular chain breakage and residue formation under high temperature and humidity conditions. Examples 1-6 all passed the 85°C / 336h heat aging test of General Motors standard GMW16865-2017 and the GMW14124 cycle I high temperature and humidity environment test, with the peel force maintained within a suitable range of 700-1200g / 25mm and no residue generated.

[0055] (2) A unique two-stage crosslinking process; The peroxide crosslinking agent and antioxidant are added in two stages. DCP is added first to complete the crosslinking reaction, and then the antioxidant is added. This avoids the problem of free radicals competing with each other, which leads to a decrease in crosslinking density. This ensures that the hot melt pressure-sensitive adhesive has both excellent crosslinking structure and anti-aging properties.

[0056] (3) Introduce the organic barrier agent BETT-68; By adding BETT-68 to the surface layer, white support layer, and sun-resistant support layer, a dense crystalline structure is formed in the polyolefin substrate through its property of regulating the crystallization behavior of polyolefins. This reduces the water vapor permeability by 20-25%, effectively preventing water molecules from penetrating into the pressure-sensitive adhesive layer and preventing chain breakage caused by the plasticizing effect of water molecules.

[0057] (4) Improve scratch resistance; Adding highly transparent and glossy scratch-resistant agent FF-99 or ultra-high molecular weight polyethylene scratch-resistant agent X188 to the surface of the color-changing film significantly improves the scratch resistance of polyolefins. Tests show that adding 3% of scratch-resistant agent FF-99 or X188 can achieve a scratch resistance level of 10N.

[0058] (5) Adding inorganic microspheres facilitates secondary film application and air venting; By adding micro-fine inorganic glass beads to hot melt pressure-sensitive adhesive, the color-changing film can be easily peeled off without deformation when a second film is needed, and the peel force remains almost unchanged. This solves the practical problem of inaccurate application and the need to redo the process when applying the film manually. At the same time, it can effectively release air during the film application process.

[0059] (6) Optimized four-layer co-extrusion structure design; The color-changing film employs a four-layer co-extrusion structure. The sun-resistant support layer contains a sun-resistant carbon black masterbatch to block ultraviolet rays, while the white support layer contains titanium dioxide masterbatch to block UV radiation and enhance the surface color. These two layers work together to form a double barrier. The support layer uses a mixture of mLLDPE, LLDPE, and LDPE, with a tensile strength greater than 20 MPa and an elongation at break greater than 500%, balancing mechanical properties and blown film forming stability. Color masterbatch is added to the surface layer to represent various desired colors, and an ethylene-silicone copolymer is also incorporated for easy unwinding.

[0060] (7) Environmentally friendly dry production; It adopts a four-layer co-extrusion blown film forming process, which does not use organic solvents, thus reducing VOCs solvent emissions from the source and meeting green and environmental protection requirements.

[0061] (8) Optional PET film lamination process to improve surface quality; A PET film can be laminated onto the outer surface of the color-changing film using a hot-melt lamination process, which can further improve the surface smoothness and increase the gloss. Attached Figure Description

[0062] Figure 1 This is a schematic diagram of the structure of the four-layer co-extrusion blown film forming machine used in the manufacturing method of the self-adhesive automotive color change film that can be used in high temperature and high humidity environments for long-term use, according to the present invention.

[0063] Figure 2 This is a process flow diagram of the hot melt pressure-sensitive adhesive chemical crosslinking process (two-stage crosslinking process) in the manufacturing method of the self-adhesive automotive color change film that can be used in high temperature and high humidity environments for long-term use, according to the present invention.

[0064] Figure 3 This is a flowchart of the electron beam irradiation crosslinking process of the hot melt pressure-sensitive adhesive in the manufacturing method of the self-adhesive automotive color-changing film that can be used in high temperature and high humidity environments for long-term use, according to the present invention.

[0065] Figure 4 This is a schematic diagram of the manufacturing method steps in Embodiment 1 of the present invention.

[0066] Figure 5 This is a cross-sectional schematic diagram of the four-layer structure of the color-changing film in Embodiment 1 of the present invention.

[0067] Figure 6 This is a schematic diagram of the optional composite PET film process for the color-changing film of Embodiment 1 of the present invention.

[0068] Figure 1 , Figure 5 , Figure 6 middle: 1. Four-layer co-extrusion blown film forming machine; 2. Four single-screw extruders; 3. Air ring; 4. Bubble stabilizer; 5. Film bubble; 6. Herringbone plate; 7. Traction roller; 8. Guide roller; 9. Rewinding device; 10. Color-changing film; 11. Surface layer; 12. White support layer; 13. Sun-resistant support layer; 14. Hot melt pressure-sensitive adhesive layer; 15. Silicone rubber pressure roller; 16. PET film unwinding roller; 17. Heated mirror roller; 18. Silicone rubber peeling roller; 19. Rewinding roller; 20. Guide roller. Detailed Implementation

[0069] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.

[0070] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0071] This invention provides a method for manufacturing a self-adhesive automotive color-changing film that can withstand long-term use in high-temperature and high-humidity environments. The color-changing film comprises a four-layer co-extruded structure, consisting of a hot-melt pressure-sensitive adhesive layer, an intermediate support layer, and a surface layer from the inside out. The manufacturing method includes three core process steps: Step 1, Preparation process of cross-linked hot melt pressure-sensitive adhesive: Chemical cross-linking with dicumyl peroxide (DCP) or electron beam irradiation cross-linking is used to form a three-dimensional network structure between hydrogenated styrene block elastomer (SEBS) and hydrogenated aliphatic C5 petroleum resin, and a two-stage feeding process is used to avoid the interference of antioxidants on the cross-linking reaction. Step 2, Formulation process of the surface and intermediate support layer composition: Add hindered amine light stabilizer, compound antioxidant and organic barrier agent BETT-68 to the polyolefin substrate to synergistically improve aging resistance and water vapor barrier performance. Step 3, Four-layer co-extrusion blown film forming process: The above four layers of material are fed separately through four single-screw extruders, and after being combined by the four co-extrusion dies, they are blown into film in one go. After cooling, traction and winding, the finished color-changing film is obtained.

[0072] Alternatively, a PET film lamination process can be selected: after the four layers of co-extrusion die heads are joined together and blown into shape in one go, the four layers of color-changing film are laminated with a PET film on one side of a hot melt lamination machine equipped with heated mirror rollers.

[0073] While self-adhesive color-changing films can be formed using casting and blown film molding, the biggest problem with casting is the difference in tensile strength between the longitudinal and transverse directions. The longitudinal tensile strength is significantly greater than the transverse tensile strength, making it prone to longitudinal tearing due to unidirectional stretching. Therefore, step 3 of this invention preferably uses blown film molding to minimize the occurrence of film breakage. The extruder screw processing temperature is preferably 160–180°C, with a blow-up ratio of 2–3 and a draw ratio of 4–6.

[0074] In step 1, when using dicumyl peroxide (DCP) for chemical crosslinking, to ensure uniform mixing of DCP in the mixture of hydrogenated styrene-butadiene block copolymer (SEBS) and hydrogenated aliphatic C5 petroleum resin, industrial ethanol is used to dissolve DCP at a mass ratio of 5:1. The dissolution rate is rapid, taking only 10 minutes at room temperature. Then, an ethanol solution containing 0.2% or 0.3% DCP is mixed again with the SEBS and C5 petroleum resin mixture until homogeneous. During high-temperature extrusion granulation, the DCP decomposes to generate free radicals, initiating a crosslinking reaction between the styrene block elastomer molecular chains, forming a three-dimensional network structure composed of carbon-carbon crosslinks. The amount of DCP added is 0.2% or 0.3%.

[0075] To prevent the free radicals generated by the simultaneous addition of peroxide and antioxidant from reacting with each other and causing a decrease in crosslinking density, a two-stage crosslinking process is adopted: the addition of peroxide and antioxidant is carried out in two stages: in the first stage, after adding dicumyl peroxide, the crosslinking is completed by extrusion granulation; in the second stage, the antioxidant is added before film formation.

[0076] like Figure 2 As shown, the two-stage crosslinking process of the present invention includes a first-stage crosslinking stage and a second-stage antioxidant addition stage. The crosslinking stage includes: firstly, adding dicumyl peroxide (DCP) (dissolved in ethanol and mixed with hydrogenated styrene-butadiene block copolymer (SEBS) and hydrogenated aliphatic C5 petroleum resin) to the formulation, and then granulating it in a twin-screw extruder. When the extruder screw temperature reaches 160-170°C, the peroxide bonds of DCP rapidly and homolytically cleave to generate free radicals, initiating a crosslinking reaction between SEBS molecules. After granulation, the DCP is fully crosslinked, the free radicals in the system are completely consumed, and the crosslinked network is stably formed.

[0077] The antioxidant addition stage includes: adding powdered antioxidants (hindered phenolic primary antioxidant AO-80 and thioester auxiliary antioxidant 412S) to the prepared hot-melt pressure-sensitive adhesive granules and mixing them evenly; finally, forming a film in a casting or blown film forming machine. At this point, the SEBS network has been formed, and the C5 petroleum resin and antioxidants cannot interfere with the chemical crosslinking; they only play a role in uniformly penetrating and dispersing within the crosslinked SEBS network, thus increasing adhesion, plasticizing, and preventing oxidation.

[0078] The two-stage crosslinking process is designed to avoid interference from C5 petroleum resin and antioxidants on the chemical crosslinking reaction, ensuring that the final material has both excellent crosslinking and bonding properties.

[0079] In addition to the aforementioned chemical crosslinking method of DCP, the present invention can also employ physical crosslinking via electron beam irradiation as an alternative. For example... Figure 3As shown, in the one-stage process of electron beam irradiation crosslinking, the antioxidant is mixed evenly with SEBS and C5 petroleum resin before electron beam irradiation crosslinking (electron beam irradiation energy 40 kGy, and the thickness of the irradiated material does not exceed 10 cm), so that free radicals are directly generated on the polymer molecular chain and crosslinking reaction occurs to form a three-dimensional network structure.

[0080] Compared with chemical crosslinking, electron beam irradiation crosslinking has the following characteristics: the reaction is completed instantaneously, and free radicals complete the crosslinking reaction in a very short time, avoiding competition with antioxidants; the process is simple, and antioxidants can be mixed evenly with SEBS and C5 before irradiation crosslinking, without the need for step-by-step operation (i.e., one-stage operation); electron beams have good penetration and can uniformly generate free radicals inside the material to form a uniform crosslinking network.

[0081] When using the two-stage process of electron beam irradiation crosslinking: first, SEBS and C5 petroleum resin are mixed evenly together and then subjected to electron beam irradiation crosslinking to ensure crosslinking density; then, antioxidants are added, and then hot melt pressure-sensitive adhesive particles are extruded at high temperature.

[0082] To address the issue of inaccurate application and the need for reapplication when manually applying automotive paint protection film, fine inorganic glass microspheres (16μm in diameter, 0.3% addition) can be added to the hot-melt pressure-sensitive adhesive. Under normal application conditions, the microspheres are embedded in the pressure-sensitive adhesive layer, without affecting the effective contact area between the adhesive and the paint surface. When it's necessary to peel off the film, the microspheres act as fulcrums, reducing the actual contact area between the adhesive and the paint, lowering the peel force, and making the film easier to peel off without deformation. It also effectively releases air, improving the smoothness of the applied film.

[0083] To improve the surface hardness and scratch resistance of the color-changing film, FF-99, an anti-scratch agent, was added to the surface of the color-changing film, which significantly improved the defect of polyolefins being not scratch-resistant.

[0084] The main raw materials used in the manufacturing method of this invention are as follows (all are commercially available industrial products): Elastomer: Hydrogenated styrene-butadiene block copolymer (SEBS), using Kraton G1645 (melt index (230℃ / 5kg) of 13g / 10min) from the USA; and Zhongli S6553 (melt index (230℃ / 5kg) of 12g / 10min) from Zhejiang.

[0085] Tackifying resin: Hydrogenated aliphatic C5 petroleum resin, specifically Nanjing Xintema W115C with a softening point of 115℃; or Hanwha HC120 from South Korea with a softening point of 120℃.

[0086] Metallocene linear low-density polyethylene (mLLDPE): Exxon mLLDPE 2018, melt index (190℃ / 2.16kg) is 2.0g / 10min.

[0087] Linear low-density polyethylene (LLDPE): Nanjing Yangzi LLDPE7042, melt index (190℃ / 2.16kg) is 2.0g / 10min.

[0088] Low-density polyethylene (LDPE): CNOOC LDPE2420H, melt index (190℃ / 2.16kg) is 2.0g / 10min.

[0089] Zhejiang Jiahua ethylene-organosilicon copolymer 037 has a melt index (190℃ / 2.16kg) of 4.

[0090] The matte-finish ethylene-silicone extrusion crosslinked copolymer, Chengdu Silike Technology Mi7140-1, has a melt index (190℃ / 2.16kg) of 8.0g / 10min.

[0091] Light stabilizers: Shanghai Debai New Material Technology's hindered amine light stabilizers (HALS) UV3346, UV622, and UV770.

[0092] Antioxidants: Shanghai Debai New Material Technology's compound antioxidant S2225P, thioester auxiliary antioxidant 412S, and hindered phenolic primary antioxidant AO-80.

[0093] Rutile titanium dioxide masterbatch: Shanghai Luxiao New Materials JO9894C, melt flow index 6.0 g / 10 min.

[0094] Crosslinking agent: dicumyl peroxide (DCP), industrial grade, Shanghai Bojing Chemical.

[0095] Organic barrier agent: BETT-68, Shanghai Baiqi Trading Co., Ltd.

[0096] Scratch-resistant agent: FF-99, Shanghai Baiqi Trading Co., Ltd.

[0097] Scratch-resistant agent: Ultra-high molecular weight polyethylene X188, X201, Dongguan Xiangyi.

[0098] Hollow glass microspheres: Zhengzhou Shenglait New Materials.

[0099] Color masterbatch: Ningbo color masterbatch, Guangdong Meilian.

[0100] Solvent: Industrial ethanol, commercially available.

[0101] Lightfast carbon black masterbatch: commercially available, carbon black concentration 30%.

[0102] The present invention uses the following test methods to evaluate various properties of the color-changing film: (1) Crosslinking degree test method: Performed according to GB / 18474 standard. Weigh a certain amount of hydrogenated styrene-butadiene block copolymer (SEBS) with an added amount of 0.2% dicumyl peroxide (DCP) and a certain amount of hot melt pressure-sensitive adhesive particles after granulation of hydrogenated aliphatic C5 petroleum resin, and add them to a three-necked flask. In a constant temperature water bath, insert a reflux tube into the three-necked flask, extract the uncrosslinked part with boiling xylene, take it out, dry it, and weigh the gel part. When using electron beam irradiation for crosslinking, the energy absorbed by a certain formulation (kGy) can be selected, and then compared with chemical crosslinking to determine whether it is suitable.

[0103] (2) Peel force test method: in accordance with GB2792-2014 standard.

[0104] (3) Tensile strength test method: in accordance with GB / T 30776-2014 standard.

[0105] (4) Test method for elongation at break: in accordance with GB / T 30776-2014 standard.

[0106] (5) Surface scratch resistance test method: Ford FLTM BN 108-13 or refer to GB / T44507 Determination and evaluation of scratch resistance of artificial leather and synthetic leather surfaces.

[0107] (6) Thermal aging test method: Volkswagen AG Technical Standard QP-R015:2013-05: 80℃, 16h; General Motors Technical Standard GMW 16865-2017: 85℃, 336h.

[0108] (7) High temperature and high humidity environment test method: Volkswagen Corporation Technical Standard QP-R015:2013-05; General Motors technical standards GMW 16865-2017 and GMW 14124-2022 Cycle I.

[0109] (8) Xenon arc lamp aging test method: Volkswagen Corporation Technical Standard QP-R015:2013-05; General Motors technical standards GMW 16865-2017 and SAE J2527 SEP2017.

[0110] The product specifications and implementation equipment of the color-changing film manufactured by the method of this invention are as follows: The maximum width of the self-adhesive automotive paint color change film is 1520mm, and the common thickness is 0.16mm. It can be cut into various widths according to user requirements.

[0111] The inner diameter of the paper tube at the factory is 76mm, and the wall thickness of the paper tube is not less than 8mm.

[0112] Common peel force: 1000g / 25mm.

[0113] The film has a colorful appearance and a smooth surface.

[0114] Factory packaging: 16m / roll.

[0115] A four-layer co-extrusion blown film forming machine with a folding diameter of 1600mm and upward rotation is selected. The four-layer co-extrusion blown film forming machine includes a four-layer co-extrusion blown film forming main unit, which is equipped with four single-screw extruders, which are used to supply materials for the surface layer, white support layer, sun-resistant support layer and hot melt pressure-sensitive adhesive layer, respectively. The materials are extruded through the four-layer co-extrusion dies to form film bubbles. During the rising process, the film bubbles are cooled and shaped by the air ring and stabilized by the bubble stabilizer. Then, the film bubbles are gathered and flattened by the herringbone plate, pulled by the traction roller, guided by the guide roller, and finally wound by the winding device to obtain the finished color-changing film.

[0116] Example 1: Example 1 provides a method for manufacturing a self-adhesive automotive color-changing film that can withstand long-term use in high-temperature and high-humidity environments, such as... Figure 4 As shown, it includes the following steps: Step S1, prepare the cross-linked hot melt pressure-sensitive adhesive composition: S1-1, DCP Dissolution: Take 0.2 parts by mass of dicumyl peroxide (DCP), add 1.0 parts by mass of industrial ethanol (ethanol to DCP mass ratio is 5:1), stir at room temperature for 10 minutes until completely dissolved to obtain DCP ethanol solution.

[0117] S1-2, Mixing and Drying: 72 parts by weight of hydrogenated styrene-butadiene block copolymer (SEBS) G1645 and 28 parts by weight of hydrogenated aliphatic C5 petroleum resin HC120 were added to a high-speed mixer and stirred for 5 minutes; then the DCP ethanol solution obtained in S1-1 was evenly sprayed into the mixture and stirred for another 10 minutes; the mixture was transferred to a mixer with a drying function and dried at 60°C for 30 minutes until the ethanol was completely evaporated.

[0118] S1-3, Chemical cross-linking granulation: The dried mixture is fed into a twin-screw extruder for granulation. The extruder screw temperature is set to 160-170℃. At high temperature, the peroxide bonds of DCP are homolytically broken to generate free radicals, which trigger the cross-linking reaction between SEBS molecules to form a three-dimensional network structure, thus obtaining cross-linked hot melt pressure-sensitive adhesive particles.

[0119] S1-4, Antioxidant Addition (Second Stage): The cross-linked hot melt pressure-sensitive adhesive particles obtained in S1-3 are put into a mixer, and 0.3 parts by weight of hindered phenolic main antioxidant AO-80, 0.3 parts by weight of thioester auxiliary antioxidant 412S, and 0.3 parts by weight of inorganic glass microspheres (16μm in diameter) are added. The mixture is then mixed evenly to obtain the final cross-linked hot melt pressure-sensitive adhesive composition.

[0120] Step S2: Prepare the surface composition, the sun-resistant support layer composition, and the white support layer composition: S2-1, Preparation of surface composition: 80 parts by weight of low-density polyethylene (LDPE) 2420H, 10 parts by weight of linear low-density polyethylene (LLDPE) 7042, 10 parts by weight of ethylene-organosilicon copolymer 037, 3 parts by weight of scratch resistant agent FF-99, 0.3 parts by weight of hindered amine light stabilizer (HALS) UV3346, and 0.8 parts by weight of compound antioxidant S2225P are added to a high-speed mixer and mixed evenly with an appropriate amount of color masterbatch to obtain the surface composition.

[0121] S2-2, Preparation of the white support layer composition: 20 parts by weight of low-density polyethylene (LDPE) 2420H, 38 parts by weight of linear low-density polyethylene (LLDPE) 7042, 25 parts by weight of metallocene linear low-density polyethylene (mLLDPE) 2018HA, 15 parts by weight of rutile titanium dioxide masterbatch (titanium dioxide concentration 65%), 2.0 parts by weight of organic barrier agent BETT-68, 0.3 parts by weight of hindered amine light stabilizer (HALS) UV3346, and 0.8 parts by weight of compound antioxidant S2225P were added to a high-speed mixer and mixed evenly to obtain the white support layer composition.

[0122] S2-3, Preparation of the sun-resistant support layer composition: 20 parts by weight of low-density polyethylene (LDPE) 2420H, 38 parts by weight of linear low-density polyethylene (LLDPE) 7042, 25 parts by weight of metallocene linear low-density polyethylene (mLLDPE) 2018HA, 8 parts by weight of carbon black masterbatch with a 30% concentration of sun-resistant carbon black, 2.0 parts by weight of organic barrier agent BETT-68, 0.3 parts by weight of hindered amine light stabilizer (HALS) UV3346, and 0.8 parts by weight of compounded antioxidant S2225P are added to a high-speed mixer and mixed evenly to obtain the sun-resistant support layer composition.

[0123] Step S3, four-layer co-extrusion molding: S3-1, Extruder settings: (e.g., ...) Figure 1As shown, the surface composition obtained in step S2, the white support layer and the sun-resistant support layer composition, and the cross-linked hot melt pressure-sensitive adhesive composition obtained in step S1 are respectively put into four single-screw extruders 2 of the four-layer co-extrusion blown film forming host 1, and the processing temperature of each extruder screw is set to 160-180°C.

[0124] S3-2, Co-extrusion blown film: Four layers of material are co-extruded through four co-extrusion dies of four single screw extruders 2, cooled and shaped by air ring 3, with the blow-up ratio set to 2.5 and the traction ratio set to 5, and the blown film is formed to obtain a layered film bubble 5.

[0125] S3-3, Cooling and winding: After the film bubble 5 is cooled by the air ring 3, it is stabilized by the bubble stabilizer 4, gathered by the herringbone plate 6, pulled by the traction roller 7, guided by the guide roller 8, and finally wound by the winding device 9 to obtain the finished color-changing film 10.

[0126] Step S4, PET film lamination process (optional): as follows Figure 6 As shown, the color-changing film 10 obtained in step S3 is conveyed to the hot melt laminating machine. The PET film is released from the PET film unwinding roller 16, guided by the guide roller 20, and then hot-pressed onto one side of the surface layer 11 of the color-changing film 10 under the pressure of the heated mirror roller 17 (surface temperature 80-120℃) and the silicone rubber pressure roller 15. The lamination pressure is 0.2-0.5MPa. After lamination, the excess tension is peeled off by the silicone rubber peeling roller 18, and finally the color-changing film product with the laminated PET film is obtained by the winding roller 19.

[0127] Example 1 also provides a long-term, high-temperature and high-humidity resistant self-adhesive automotive color-changing film manufactured by the method described in Example 1, such as... Figure 5 As shown, the structure includes four layers from the outside in: the color-changing film 10 consists of a surface layer 11, a white support layer 12, a sun-resistant support layer 13, and a hot-melt pressure-sensitive adhesive layer 14. The surface layer 11 has a thickness of 0.01 mm, the white support layer 12 and the sun-resistant support layer 13 have a combined thickness of 0.138 mm, the hot-melt pressure-sensitive adhesive layer 14 has a thickness of 0.012 mm, and the total thickness is 0.16 mm. The formulation (mass%) of the surface layer 11 includes: 80% low-density polyethylene (LDPE) 2420H, 10% linear low-density polyethylene (LLDPE) 7042, 10% ethylene-silicone copolymer 037, 3% scratch resistant agent FF-99, 0.3% hindered amine light stabilizer (HALS) UV3346, and 0.8% compounded antioxidant S2225P.

[0128] The formulation (parts by weight) of the white support layer 12 includes: 20% low-density polyethylene (LDPE) 2420H, 38% linear low-density polyethylene (LLDPE) 7042, 25% metallocene linear low-density polyethylene (mLLDPE) 2018HA, 15% rutile titanium dioxide masterbatch (titanium dioxide concentration 65%), 2.0% organic barrier agent BETT-68, 0.3% hindered amine light stabilizer (HALS) UV3346, and 0.8% compounded antioxidant S2225P.

[0129] The formulation (mass%) of the sun-resistant support layer 13 includes: low-density polyethylene (LDPE) 2420H 20%, linear low-density polyethylene (LLDPE) 7042 38%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 25%, carbon black masterbatch with a sun-resistant carbon black concentration of 30% 8%, organic barrier agent BETT-68 2.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, and compounded antioxidant S2225P 0.8%.

[0130] The formulation (mass%) of the hot-melt pressure-sensitive adhesive layer 14 includes: hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72%, hydrogenated aliphatic C5 petroleum resin HC120 28%, dicumyl peroxide (DCP) 0.2%, thioester auxiliary antioxidant 412S 0.3%, hindered phenolic primary antioxidant AO-80 0.3%, and inorganic glass microspheres (diameter 16μm) 0.3%.

[0131] Performance test results show: unwinding force <15g / 25mm, peel force 1000g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, no adhesive residue in the General Motors technical standard GMW 16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAEJ2527 SEP2017 xenon arc lamp aging test.

[0132] Example 2: The manufacturing methods of Example 2 and Example 1 are basically the same, except that the formulation and thickness of each layer are adjusted: Surface formulation (mass%): Low-density polyethylene (LDPE) 2420H 80%, linear low-density polyethylene (LLDPE) 7042 20%, ethylene-silicone copolymer 037 15%, scratch resistant agent FF-99 3%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%, and appropriate amount of color masterbatch.

[0133] White support layer 12 formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 18%, linear low-density polyethylene (LLDPE) 7042 37%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 28%, rutile titanium dioxide masterbatch (titanium dioxide concentration 65%) 15%, organic barrier agent BETT-68 5.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0134] Sun-resistant support layer 13 formulation (mass%): Low-density polyethylene (LDPE) 2420H 18%, linear low-density polyethylene (LLDPE) 7042 37%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 28%, carbon black masterbatch with 30% sun-resistant carbon black concentration 8%, organic barrier agent BETT-68 5.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0135] Hot melt pressure-sensitive adhesive layer formulation (mass%): hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72%, hydrogenated aliphatic C5 petroleum resin HC120 28%, dicumyl peroxide (DCP) 0.2%, thioester auxiliary antioxidant 412S 0.3%, hindered phenolic primary antioxidant AO-80 0.3%.

[0136] Layer thickness: 0.01mm for the surface layer, 0.135mm for the white support layer 12 and the sun-resistant support layer 13 combined, 0.015mm for the hot melt pressure-sensitive adhesive layer, and 0.16mm for the total thickness.

[0137] Performance test results: Unwinding force <15g / 25mm, peel force 1200g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, good air venting effect during film application, no adhesive residue in the General Motors technical standard GMW16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAE J2527 SEP2017 xenon arc lamp aging test.

[0138] Example 3: The manufacturing methods of Example 3 and Example 1 are basically the same, except that the formulation and thickness of each layer are adjusted: Surface formulation (mass %): Low-density polyethylene (LDPE) 2420H 70%, linear low-density polyethylene (LLDPE) 7042 30%, high-transparency ethylene-silicone copolymer 037 20%, scratch resistant agent FF-99 3%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0139] White support layer 12 formulation (mass%): Low-density polyethylene (LDPE) 2420H 17%, linear low-density polyethylene (LLDPE) 7042 36%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 30%, rutile titanium dioxide masterbatch (titanium dioxide concentration 65%) 15%, organic barrier agent BETT-68 7.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0140] Sun-resistant support layer 13 formulation (mass%): Low-density polyethylene (LDPE) 2420H 17%, linear low-density polyethylene (LLDPE) 7042 36%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 30%, carbon black masterbatch with 30% sun-resistant carbon black concentration 8%, organic barrier agent BETT-68 7.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0141] Hot melt pressure-sensitive adhesive layer formulation (mass%): Hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72%, hydrogenated aliphatic C5 petroleum resin HC120 28%, dicumyl peroxide (DCP) 0.3%, thioester auxiliary antioxidant 412S 0.3%, hindered phenolic primary antioxidant AO-80 0.3%.

[0142] Layer thickness: 0.01mm for the surface layer, 0.136mm for the white support layer 12 and the sun-resistant support layer 13 (hereinafter referred to as the intermediate support layer), 0.014mm for the hot melt pressure-sensitive adhesive layer, and 0.16mm for the total thickness.

[0143] Performance test results: Unwinding force <15g / 25mm, peel force 950g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, no adhesive residue in the General Motors technical standard GMW 16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAE J2527SEP2017 xenon arc lamp aging test.

[0144] Example 4: The manufacturing methods of Example 4 and Example 1 are basically the same, except that the formulation and thickness of each layer are adjusted: Surface formulation (mass%): Low-density polyethylene (LDPE) 2420H 60%, linear low-density polyethylene (LLDPE) 7042 40%, ethylene-silicone copolymer 037 10%, scratch resistant agent FF-99 3%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%, and appropriate amount of color masterbatch.

[0145] White support layer 12 formulation (mass%): Low-density polyethylene (LDPE) 2420H 16%, linear low-density polyethylene (LLDPE) 7042 35%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 32%, rutile titanium dioxide masterbatch (titanium dioxide concentration 65%) 15%, organic barrier agent BETT-68 10.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0146] Sun-resistant support layer 13 formulation (mass%): Low-density polyethylene (LDPE) 2420H 16%, linear low-density polyethylene (LLDPE) 7042 35%, metallocene linear low-density polyethylene (mLLDPE) 2018HA 32%, carbon black masterbatch with 30% sun-resistant carbon black concentration 8%, organic barrier agent BETT-68 10.0%, hindered amine light stabilizer (HALS) UV3346 0.3%, compounded antioxidant S2225P 0.8%.

[0147] Hot melt pressure-sensitive adhesive layer formulation (mass%): Hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72%, hydrogenated aliphatic C5 petroleum resin HC120 28%, dicumyl peroxide (DCP) 0.4%, thioester auxiliary antioxidant 412S 0.3%, hindered phenolic primary antioxidant AO-80 0.3%.

[0148] Layer thickness: 0.01mm for the surface layer, 0.137mm for the intermediate support layer, 0.013mm for the hot melt pressure-sensitive adhesive layer, and 0.16mm for the total thickness.

[0149] Performance test results: Unwinding force <15g / 25mm, peel force 800g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, good air venting effect during film application, no adhesive residue in the General Motors technical standard GMW16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAE J2527 SEP2017 xenon arc lamp aging test.

[0150] Example 5: The manufacturing methods of Example 5 are basically the same as those of Example 1, except that the formulation and thickness of each layer are adjusted: Surface formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 100, ethylene-silicone copolymer 037 15, scratch resistant agent FF-99 3, hindered amine light stabilizer (HALS) UV3346 0.4, compound antioxidant S2225P 0.4, and appropriate amount of color masterbatch.

[0151] White support layer 12 formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 17, linear low-density polyethylene (LLDPE) 7042 38, metallocene linear low-density polyethylene (mLLDPE) 2018HA 28, rutile titanium dioxide masterbatch (titanium dioxide concentration 65%) 15, organic barrier agent BETT-68 12.0, hindered amine light stabilizer (HALS) UV3346 0.6, compound antioxidant S2225P 0.8.

[0152] Sun-resistant support layer 13 formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 17, linear low-density polyethylene (LLDPE) 7042 28, metallocene linear low-density polyethylene (mLLDPE) 2018HA 38, carbon black masterbatch with 30% sun-resistant carbon black concentration 8, organic barrier agent BETT-68 12.0, hindered amine light stabilizer (HALS) UV3346 0.3, compounded antioxidant S2225P 0.8.

[0153] The hot-melt pressure-sensitive adhesive layer 14 formulation (parts by weight): hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72, hydrogenated aliphatic C5 petroleum resin HC120 28, dicumyl peroxide (DCP) 0.2, thioester auxiliary antioxidant 412S 0.4, hindered phenolic primary antioxidant AO-80 0.3, and inorganic glass microspheres (16μm in diameter) 0.3.

[0154] Layer thickness: 0.01mm for the surface layer, 0.137mm for the intermediate support layer, 0.0135mm for the hot melt pressure-sensitive adhesive layer, and 0.16mm for the total thickness.

[0155] Performance test results: Unwinding force <15g / 25mm, peel force 700g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, good air venting effect during film application, no adhesive residue in the General Motors technical standard GMW16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAE J2527 SEP2017 xenon arc lamp aging test.

[0156] Example 6: The manufacturing methods of Example 6 and Example 1 are basically the same, except that the formulation and thickness of each layer are adjusted, and the hot melt pressure-sensitive adhesive is crosslinked by electron beam irradiation instead of chemical crosslinking of DCP. Surface formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 100, ethylene-silicone copolymer Mi7140-1 20, scratch resistant agent FF-99 3, hindered amine light stabilizer (HALS) UV3346 0.4, compounded antioxidant S2225P 0.4, and appropriate amount of color masterbatch.

[0157] White support layer 12 formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 19, linear low-density polyethylene (LLDPE) 7042 38, metallocene linear low-density polyethylene (mLLDPE) 2018HA 26, rutile titanium dioxide masterbatch (titanium dioxide concentration 65%) 15, organic barrier agent BETT-68 12.0, hindered amine light stabilizer (HALS) UV3346 0.3, compound antioxidant S2225P 0.8.

[0158] Sun-resistant support layer 13 formulation (parts by weight): Low-density polyethylene (LDPE) 2420H 17, linear low-density polyethylene (LLDPE) 7042 26, metallocene linear low-density polyethylene (mLLDPE) 2018HA 40, carbon black masterbatch with 30% sun-resistant carbon black concentration 8, organic barrier agent BETT-68 12.0, hindered amine light stabilizer (HALS) UV3346 0.3, compounded antioxidant S2225P 0.8.

[0159] The hot-melt pressure-sensitive adhesive layer 14 formulation (parts by weight) consists of: hydrogenated styrene-butadiene block copolymer (SEBS) G1645 72, hydrogenated aliphatic C5 petroleum resin HC120 28, crosslinked by electron beam irradiation at an energy of 40 kGy, without added DCP, thioester auxiliary antioxidant 412S 0.4, hindered phenolic primary antioxidant AO-80 0.4, and inorganic glass microspheres (16 μm in diameter) 0.3.

[0160] Layer thickness: 0.01mm for the surface layer, 0.137mm for the intermediate support layer, 0.015mm for the hot melt pressure-sensitive adhesive layer, and 0.16mm for the total thickness.

[0161] Performance test results: Unwinding force <15g / 25mm, peel force 1100g / 25mm, tensile strength >20MPa, elongation at break >500%, no exudation, scratch resistance up to 10N, good air venting effect during film application, no adhesive residue in the General Motors technical standard GMW16865-2017 heat aging test, no adhesive residue in the GMW 14124-2022 cycle I high temperature and humidity environment test, and no adhesive residue in the SAE J2527 SEP2017 xenon arc lamp aging test.

[0162] In all of the above Examples 1 to 6, 0.3% of 16μm glass microspheres were added to the hot melt pressure-sensitive adhesive, which resulted in a good air venting effect during film application; when the scratch-resistant agent FF-99 was added, the surface of the color-changing film was not easily damaged when scratched.

[0163]

[0164]

[0165] Comparative Example 1 (without dicumyl peroxide crosslinking): The formulation of Comparative Example 1 is basically the same as that of Example 1, except that dicumyl peroxide (DCP) is not added to the hot melt pressure-sensitive adhesive (the amount of crosslinking agent added is 0).

[0166] Test results of the color-changing film manufactured by the method of Comparative Example 1 showed that the peel strength was 300g / 25mm, there was exudation, adhesive residue was found in the heat aging test according to General Motors technical standard GMW 16865-2017, and adhesive residue was found in the cycle I high temperature and high humidity environment test according to GMW 14124-2022.

[0167] Comparative Example 2 (without dicumyl peroxide crosslinking and without glass microspheres): The formulation of Comparative Example 2 is basically the same as that of Example 2, except that dicumyl peroxide (DCP) is not added to the hot melt pressure-sensitive adhesive (the amount of crosslinking agent added is 0), and glass microspheres are not added.

[0168] The test results of the color-changing film manufactured by the method of Comparative Example 2 showed that the peel strength was 500g / 25mm, there was exudation, the air venting effect was poor when the film was applied, and there was adhesive residue in the heat aging test according to the General Motors technical standard GMW 16865-2017 and the GMW14124-2022 cycle I high temperature and high humidity environment test.

[0169] Comparative Example 3 (without dicumyl peroxide crosslinking and without glass microspheres): The formulation of Comparative Example 3 is basically the same as that of Example 3, except that dicumyl peroxide (DCP) is not added to the hot melt pressure-sensitive adhesive (the amount of crosslinking agent added is 0), and glass microspheres are not added.

[0170] The test results of the color-changing film manufactured by the method of Comparative Example 3 showed that the peel strength was 600g / 25mm, there was exudation, the air venting effect was poor when the film was applied, and there was adhesive residue in the heat aging test according to the General Motors technical standard GMW 16865-2017 and the GMW14124-2022 cycle I high temperature and high humidity environment test.

[0171] When no dicumyl peroxide (DCP) was added for crosslinking in Comparative Examples 1-3, adhesive residues were generated in the color-changing films under high temperature and high humidity environments, indicating that crosslinking technology is the key to solving the adhesive residue problem.

[0172] Comparative Example 4 (excessive addition of dicumyl peroxide): The formulation of Comparative Example 4 is basically the same as that of Example 4, except that the amount of dicumyl peroxide (DCP) added is 0.6%.

[0173] Test results for the color-changing film manufactured by method 4 in Comparative Example 4: The peel strength dropped sharply to 60 g / 25 mm, the adhesive layer hardened, and the elongation at break dropped to >400%. Although there was no adhesive residue, the bonding performance was severely impaired.

[0174] Excessive addition of dicumyl peroxide (DCP) can lead to over-crosslinking, causing the adhesive layer to harden and peel strength to drop significantly. The amount of DCP should be controlled within a reasonable range of 0.1% to 0.6%.

[0175] Comparative Example 5 (Electron Beam Irradiation Energy Too Low): The formulation of Comparative Example 5 is basically the same as that of Example 5, except that the hot melt pressure-sensitive adhesive is crosslinked by electron beam irradiation with an energy of 20 kGy and no DCP is added.

[0176] Test results of the color-changing film manufactured by the method of Comparative Example 5 showed that the peel strength was 40g / 25mm, there was slight adhesive residue, the adhesive layer hardened, and the elongation at break was <350%.

[0177] Comparative Example 6 (Electron Beam Irradiation Energy Too High): The formulation of Comparative Example 6 is basically the same as that of Example 6, except that the hot melt pressure-sensitive adhesive is crosslinked by electron beam irradiation with an energy of 60 kGy and no DCP is added.

[0178] Test results of the color-changing film manufactured by the method of Comparative Example 6 showed that the peel strength was 30g / 25mm, the adhesive layer hardened, and the elongation at break was <300%.

[0179] Comparative Example 7: The formulation of Comparative Example 7 is basically the same as that of Example 1, except that the organic barrier agent BETT-68 is not added to the sun-resistant support layer 13 and the white support layer 12. Adhesive residue was found in the Cycle I high temperature and high humidity environmental test according to General Motors Technical Standard GMW 14124-2022.

[0180] Comparative Example 8: The formulation of Comparative Example 8 is basically the same as that of Example 2, except that the organic barrier agent BETT-68 is not added to the sun-resistant support layer 13 and the white support layer 12. Adhesive residue was found in the Cycle I high temperature and high humidity environmental test according to General Motors Technical Standard GMW 14124-2022.

[0181] Comparative Example 9: The formulation of Comparative Example 9 is basically the same as that of Example 3, except that the organic barrier agent BETT-68 is not added to the sun-resistant support layer 13 and the white support layer 12. Adhesive residue was found in the Cycle I high temperature and high humidity environmental test according to General Motors Technical Standard GMW 14124-2022.

[0182] In Comparative Examples 7-9, no organic barrier agent BETT-68 was added, and water vapor penetrated into the pressure-sensitive adhesive layer, resulting in adhesive residue. This indicates that barrier agents are an important technical means to prevent adhesive residue in high-temperature and high-humidity environments.

[0183] Table 2: Parameter Comparison Table for Comparative Examples 1-6

[0184]

[0185]

[0186] Analysis of the effects of crosslinking technology: As can be seen from the comparison between Examples 1-6 and Comparative Examples 1-3 in Tables 1 and 2: (1) Uncrosslinked (Comparative Examples 1-3): When dicumyl peroxide (DCP) was not added to the hot-melt pressure-sensitive adhesive for crosslinking, adhesive residue appeared in both the thermal aging test and the high temperature and humidity environment test according to General Motors' technical standards, and precipitation occurred on the film surface. This is because the molecular chains of uncrosslinked hydrogenated styrene-butadiene block copolymer (SEBS) are prone to thermal oxidative degradation under high temperature and humidity conditions. The molecular chain breaks, resulting in a decrease in cohesion, thus producing adhesive residue during peeling.

[0187] (2) Moderate crosslinking (Examples 1-6, DCP 0.2-0.4%): After moderate crosslinking with DCP, the hot-melt pressure-sensitive adhesive forms stable carbon-carbon (CC) crosslinking bonds between SEBS molecular chains, constructing a three-dimensional network structure and significantly improving cohesion. All examples passed the stringent testing of General Motors' technical standards, with no adhesive residue generated. Meanwhile, the peel strength remained within a suitable range of 700-1200 g / 25 mm, balancing adhesion and peelability.

[0188] (3) Excessive crosslinking (Comparative Examples 4-6, DCP 0.6%): When the amount of DCP added is 0.6%, the crosslinking density is too high, which leads to the hardening of the adhesive layer, a sharp decrease in peel strength (down to 60g / 25mm), and a significant decrease in elongation at break (<350%), which cannot meet the requirements for use.

[0189] Electron beam irradiation energy <20kGy (Comparative Example 5) is insufficient, resulting in slight adhesive residue. Electron beam irradiation energy >60kGy (Comparative Example 6) causes the adhesive to harden, and the peel strength drops significantly to below 30g / 25mm, failing to meet the usage requirements.

[0190] Analysis of the effects of barrier agents and scratch-resistant agents: As can be seen from the comparison of Examples 1-6 and Comparative Examples 7-9 in Tables 1 and 2: (1) No organic barrier agent BETT-68 added (Comparative Examples 7-9): In the high temperature and high humidity environment test, water vapor penetrates into the hot melt pressure-sensitive adhesive through the surface layer and the intermediate support layer, which plays a plasticizing role, increases the molecular chain spacing, accelerates the thermal oxidation degradation reaction, and leads to adhesive residue.

[0191] (2) Addition of organic barrier agent BETT-68 (Examples 1-6): BETT-68 forms an irregular mesh-like interwoven structure in the polyolefin substrate, increasing the path length of water vapor and forming a barrier. The water vapor permeability is reduced by about 20-25%, effectively preventing water molecules from damaging the pressure-sensitive adhesive and ensuring the long-term performance of the color-changing film in high temperature and high humidity environments.

[0192] (3) Without the addition of scratch-resistant agent FF-99, the surface of the color-changing film is easily damaged when scratched.

[0193] Analysis of the effects of the two-stage crosslinking process: The two-stage crosslinking process (first adding dicumyl peroxide for granulation to complete crosslinking, then adding an antioxidant before film formation) has the following advantages: (1) Avoid free radical competition: Dicumyl peroxide (DCP) and antioxidants compete with each other in the free radical reaction, and their simultaneous addition will reduce the crosslinking density. The two-stage process ensures that DCP completes the crosslinking reaction during the granulation stage, and the antioxidant is added only after the free radicals in the system are completely consumed, thus ensuring the crosslinking density.

[0194] (2) Controllable crosslinking degree: When the DCP concentration is 0.2%, the gel content is about 30-50% (tested according to GB / 18474, and the crosslinking degree is according to ASTM D2765), and the crosslinking network is stably formed.

[0195] (3) Good process compatibility: The two-stage process is compatible with existing hot melt pressure-sensitive adhesive production equipment, requiring no additional investment and easy to promote industrialization.

[0196] The technical solution of this invention systematically solves the problem of adhesive residue in automotive paint color-changing films under high temperature and humidity environments where they can be used for more than five years through the synergistic effect of "crosslinking technology + barrier technology + process optimization". All embodiments have passed the 85℃ / 336h thermal aging test of General Motors technical standard GMW 16865-2017, the GMW 14124-2022 cycle I high temperature and humidity environment test, and the SAE J2527 SEP2017 xenon arc lamp aging test, demonstrating that the color-changing film of this invention can be safely used in low-latitude tropical or subtropical regions with high temperature and humidity for more than five years.

[0197] The above description of the embodiments is provided to enable those skilled in the art to understand and use the present invention. It will be apparent to those skilled in the art that various modifications can be easily made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention are within the protection scope of the present invention.

Claims

1. A method for manufacturing a self-adhesive automotive color-changing film that can withstand high temperature and humidity environments for long-term use, characterized in that, The color-changing film includes a surface layer, a support layer, and a hot-melt pressure-sensitive adhesive layer. The hot-melt pressure-sensitive adhesive layer is cross-linked to form a chemical bond network structure, which improves cohesion and avoids the generation of residual adhesive when pasting on the automotive paint surface in a high-temperature and high-humidity environment. The crosslinking treatment forms a three-dimensional network structure in the hot melt pressure-sensitive adhesive, which is composed of polymer molecular chains connected by covalent bonds. The three-dimensional network structure inhibits the thermal motion and thermal oxidative degradation of molecular chains under high temperature conditions, and resists the plasticizing effect of water molecules on molecular chains under high temperature and high humidity conditions, thereby maintaining the cohesive stability of the hot melt pressure-sensitive adhesive.

2. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, The hot-melt pressure-sensitive adhesive layer is formed by mixing hydrogenated styrene block elastomer and hydrogenated petroleum resin and then cross-linking the mixture to form the chemical bond network structure.

3. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 2, characterized in that, The hydrogenated petroleum resin is a hydrogenated aliphatic C5 petroleum resin.

4. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, The support layer includes a white support layer and a sun-resistant support layer; preferably, the white support layer is a support layer containing titanium dioxide to block UV irradiation and enhance the surface color, and the sun-resistant support layer is a support layer containing sun-resistant carbon black to block UV.

5. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, The crosslinking treatment is performed by chemical crosslinking using peroxide as a crosslinking agent, or by physical crosslinking using irradiation.

6. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 5, characterized in that, The peroxide is dicumyl peroxide (DCP).

7. The manufacturing method of the long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 5, characterized in that, The irradiation is electron beam irradiation.

8. The manufacturing method of the long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 6, characterized in that, The use of dicumyl peroxide (DCP) as a crosslinking agent for chemical crosslinking refers to the following: after mixing DCP with hydrogenated styrene block elastomer and hydrogenated aliphatic C5 petroleum resin, the DCP is decomposed during high-temperature extrusion granulation to generate free radicals, which initiate crosslinking reactions between styrene block elastomer molecular chains, forming a three-dimensional network structure composed of carbon-carbon crosslinking bonds; preferably, the amount of DCP added is 0.2% to 0.4%.

9. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 7, characterized in that, The physical crosslinking using electron beam irradiation refers to: granulating a mixture of hydrogenated styrene block elastomer and hydrogenated aliphatic C5 petroleum resin and then irradiating it with an electron beam to directly generate free radicals on the polymer molecular chains and cause a crosslinking reaction, forming a three-dimensional network structure; preferably, the energy of the electron beam irradiation is 40 kGy, and the accumulation thickness of the irradiated material does not exceed 10 cm.

10. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, The color-changing film is formed in one step by a co-extrusion blow molding film forming process. The surface layer, support layer and hot melt pressure-sensitive adhesive layer are respectively fed by their respective extruders and then combined by a co-extrusion die to form the film.

11. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 10, characterized in that, The co-extrusion blow molding film forming process is a four-layer co-extrusion blow molding film forming process. The surface layer, white support layer, sun-resistant support layer and hot melt pressure-sensitive adhesive layer are respectively fed by their respective extruders and are combined by the four-layer co-extrusion die to form a four-layer color-changing film.

12. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 11, characterized in that, It also includes a PET film lamination process: after the four co-extrusion dies are combined into four color-changing films, one side of the four color-changing film is laminated with a PET film on a hot melt lamination machine equipped with heated mirror rollers.

13. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, Antioxidants are added to the cross-linked hot melt pressure-sensitive adhesive particles, preferably including hindered phenolic primary antioxidants and thioester auxiliary antioxidants; preferably, the amount of hindered phenolic primary antioxidant AO-80 added is 0.3% to 0.4%, and the amount of thioester auxiliary antioxidant 412S added is 0.3% to 0.4%.

14. The manufacturing method of the long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 8, characterized in that, To prevent the free radicals generated by the peroxide and antioxidant from reacting with each other and causing a decrease in crosslinking density when they are added at the same time, the addition of the peroxide and antioxidant is carried out in two stages: in the first stage, after adding dicumyl peroxide, the crosslinking is completed by extrusion granulation; in the second stage, the antioxidant is added before film formation.

15. The method for manufacturing a long-term, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 9, characterized in that, Electron beam irradiation crosslinking can be carried out in one stage, that is, the antioxidant is mixed evenly with SEBS and C5, granulated and then directly irradiated for crosslinking; or it can be carried out in two stages: first, irradiation crosslinking is carried out without adding antioxidant to ensure crosslinking density, and then antioxidant is added.

16. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that: A hindered amine light stabilizer and a compound antioxidant are added to the surface layer and support layer of the color-changing film, respectively, to synergistically reduce thermal oxidative degradation in conjunction with the antioxidant in the cross-linked hot melt pressure-sensitive adhesive. Preferably, the hindered amine light stabilizer is UV3346, with an addition amount of 0.3% to 0.4%, and the compound antioxidant is S2225P, with an addition amount of 0.4% to 0.8%.

17. The method for manufacturing a long-term, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 1, characterized in that, A color masterbatch with a required sun resistance rating of level 8 is added to the surface layer of the color-changing film. A white masterbatch with a titanium dioxide concentration of 65% is added to the white support layer to help block UV radiation. The addition of white masterbatch can also complement the various colors of the surface layer. Preferably, the amount of white masterbatch added is 15%. And / or a carbon black masterbatch with a sun-resistant carbon black concentration of 30% is added to the sun-resistant support layer to block ultraviolet rays. Preferably, the amount of carbon black masterbatch added is 8%. And / or to improve the easy unwinding performance of the color-changing film during application, an ethylene-organic silicone copolymer is added to the surface layer. Preferably, the amount added is 10% to 20%.

18. The method for manufacturing a long-term, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 1, characterized in that, An organic barrier agent is added to the surface and support layers of the color-changing film to slow down the penetration of water vapor into the hot melt pressure-sensitive adhesive and prevent the plasticizing effect of water molecules from causing the breakage of the SEBS material chain; preferably, the organic barrier agent is BETT-68, and the amount added is 2.0% to 12.0%.

19. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, A scratch-resistant agent is added to the surface of the color-changing film to improve the scratch resistance of the polyolefin; preferably, the scratch-resistant agent is FF-99 or ultra-high molecular weight polyethylene X188, and the amount added is 3%.

20. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, The support layer is a mixture of mLLDPE, LLDPE and LDPE. Preferably, the tensile strength of the color-changing film is greater than 20 MPa and the elongation at break is greater than 500%.

21. The manufacturing method of the self-adhesive automotive color-changing film with long-term use and resistance to high temperature and high humidity environments according to claim 1, characterized in that, Inorganic microspheres are added to hot melt pressure-sensitive adhesive, preferably with a diameter of 16 μm and an addition amount of 0.3%.

22. A self-adhesive automotive color-changing film resistant to high temperature and humidity environments for long-term use, manufactured by the manufacturing method according to any one of claims 1 to 21, characterized in that, The structure comprises a co-extruded layer, a support layer, and a hot-melt pressure-sensitive adhesive layer; the hot-melt pressure-sensitive adhesive layer is cross-linked to form a three-dimensional network structure, which is formed by polymer molecular chains connected by covalent bonds; preferably, the hot-melt pressure-sensitive adhesive layer shows no adhesive residue after undergoing a GMW16865 heat aging test at 85℃±2℃ / 336h and a GMW14124 cycle I high temperature and high humidity environment test.

23. The long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 22, characterized in that: The hot-melt pressure-sensitive adhesive layer has a three-dimensional network structure formed by cross-linking hydrogenated styrene block elastomer and hydrogenated petroleum resin.

24. The long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 23, characterized in that: The hydrogenated petroleum resin is a hydrogenated aliphatic C5 petroleum resin.

25. The long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 22, characterized in that: The support layer comprises a white support layer and a sun-resistant support layer; the white support layer contains rutile titanium dioxide, and the sun-resistant support layer contains sun-resistant carbon black; the surface layer and / or the white support layer and / or the sun-resistant support layer contain the organic barrier agent BETT-68; the surface layer contains the scratch-resistant agent FF-99; the surface layer contains an ethylene-organosilicon copolymer; The color-changing film showed no adhesive residue after undergoing the GMW16865, 85℃±2℃ / 336h thermal aging test and the GMW14124 cycle I high temperature and high humidity environment test, and can be used for more than five years.

26. The long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 25, characterized in that, The hot melt pressure-sensitive adhesive layer also contains inorganic microspheres, preferably with a diameter of 16 μm and an addition amount of 0.3%.

27. The long-term use, high-temperature and high-humidity resistant self-adhesive automotive color-changing film according to claim 22, characterized in that, It also includes a PET film layer, which is laminated with the surface layer to improve the surface smoothness and increase the gloss of the color-changing film.

Citation Information

Patent Citations

  • Fragrant masking tape

    CN103865428A

  • Transparent all-purpose adhesive and preparation method thereof

    CN105802554A

  • Preparation method for glutinous rice glue for wallpaper

    CN107629726A

  • Novel high-temperature-resistant strippable pressure-sensitive adhesive tape

    CN110527454A

  • Surface protective film for coated car body

    JP2000033671A